РЕЗУЛЬТАТЫ ГЕОЛОГО-БИОЛОГИЧЕСКИХ ИССЛЕДОВАНИЙ ЛЕЧЕБНЫХ ГРЯЗЕЙ ЗАЛИВА ПЕТРА ВЕЛИКОГО - Иванова В.Л.; Медведева Л.А.; Афанасьева Т.Б.; Баринов Н.Н.; Карабцов А.А. (My University, 2009)
The article presents the results of the study of sulphide deposits of curative mud in the coastal area of south-western coast of the Gulf of Peter the Great. It is shown that there is a correlation power mud deposits with an abundance and diversity in their composition of diatoms, with sulfurcontaining minerals pyrite and jarosite are authigenic. The study samples for microprobe and electron microscope has reason to believe biogenic pyrite.
Keywords: ЛЕЧЕБНЫЕ ГРЯЗИ; ДИАТОМЕИ; DIATOMS; ПИРИТ; PYRITE; ЯРОЗИТ; JAROSITE; MEDICINAL MUD; 550.7; 553.2; 615.83